2018
DOI: 10.1007/s12264-018-0312-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered Local Field Potential Relationship Between the Parafascicular Thalamic Nucleus and Dorsal Striatum in Hemiparkinsonian Rats

Abstract: The thalamostriatal pathway is implicated in Parkinson’s disease (PD); however, PD-related changes in the relationship between oscillatory activity in the centromedian-parafascicular complex (CM/Pf, or the Pf in rodents) and the dorsal striatum (DS) remain unclear. Therefore, we simultaneously recorded local field potentials (LFPs) in both the Pf and DS of hemiparkinsonian and control rats during epochs of rest or treadmill walking. The dopamine-lesioned rats showed increased LFP power in the beta band (12 Hz–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The glutamate levels were reported to be related to the gamma bands (Lally et al, 2014), while the effect of the dopaminergic and cholinergic neurons has been observed on low frequency fluctuation of LFP (Neske, 11 2016). The delta power of LFP in the ipsilateral DS was reduced by the disruption of dopamine in the resting state (Zhang et al, 2018). Although the mechanism of delta power increase in the ipsilateral DS is not clear, the change of dopaminergic or cholinergic neurons activation following the activation of striatal neurons may induce this delta power increase.…”
Section: Falff and Blp Alterationmentioning
confidence: 93%
“…The glutamate levels were reported to be related to the gamma bands (Lally et al, 2014), while the effect of the dopaminergic and cholinergic neurons has been observed on low frequency fluctuation of LFP (Neske, 11 2016). The delta power of LFP in the ipsilateral DS was reduced by the disruption of dopamine in the resting state (Zhang et al, 2018). Although the mechanism of delta power increase in the ipsilateral DS is not clear, the change of dopaminergic or cholinergic neurons activation following the activation of striatal neurons may induce this delta power increase.…”
Section: Falff and Blp Alterationmentioning
confidence: 93%
“…Abnormal functions of the striatum are closely associated with Huntington's disease and Parkinson's disease [2][3][4]. The striatum can be divided into the dorsal and ventral parts [2,5]. The dorsal striatum comprises the caudate nucleus and putamen, while the ventral striatum includes the nucleus accumbens and olfactory tubercles [6].…”
Section: Introductionmentioning
confidence: 99%
“…e animals were maintained under a 12 h reversed light/dark cycle (with darkness starting from 8:00 am) with controlled room temperature and humidity. Tap water was made available ad libitum, and food was restricted to 20 g per day to keep animal weight constant [23,24]. All procedures were performed in accordance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals and with the approval of Animal Care and Use Committee of Jianghan University.…”
Section: Animalsmentioning
confidence: 99%